Neurodidactics: an experience in inclusive education applied to ICT - Delgado-Valdivieso, Karina (2022)
The learning is based on the approaches of neurodidactics, to respond to the diversity of learning needs with the use of technological resources, as the main option to guarantee the educational service, support the community, provide protection and emotional support in children, girls and adolescents with disabilities (NNACD). It proposes an analysis that allows knowing the application of accessibility to learning in five educational institutions of Fe y Alegría, belonging to three localities of Ecuador with 212 NNACD, who, in a specific way of attention, develop their learning for life, through the qualitative research, related to Person Centered Planning (PCP). The information has been organized into three levels: equipment and connectivity, psychomotricity of the NNACD and pedagogical delivery, which allow defining the different skills assumed by the NNACD according to specific disabilities and with respect to technological accessibility. The main resources used are tablets, smartphones and computers. The use of desktop computers allows a greater field of work, especially in students with intellectual disabilities and infantile cerebral palsy, who require additional technological adaptations.